Lokasi Strategis Tempat Pembuangan Akhir Sebagai Upaya Penanggulangan Dampak Sampah Masyarakat - Muhamad Ilham; Surdin; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2023)
Tomia Island is one of a group of islands in the Wakatobi region and has an increasing waste problem. It is estimated that in the next few years the garbage on Tomia Island will cover the land if there is no follow-up from the government. In addition to the lack of trash cans in several areas of Tomia Island, the waste problem is also exacerbated because this area does not have any landfills. This resulted in cleaning workers dumping garbage in gardens and also in mountain holes called lia (holes). The aims of this study were to: 1) analyze the strategic location for the construction of landfills; and 2) describe the community's response to the construction of a final waste disposal site in Waitii Village. This research is a type of qualitative descriptive research with research respondents consisting of traditional leaders, village government representatives, sub-districts, environmental services, waste officers and the community who live around the location of the final waste disposal site chosen by the Waitii Village government. Data collection techniques in this study, namely observation, interviews and documentation. The results of this study indicate that: 1) a strategic location that complies with Indonesian national standards is in Fune, because it has complied with regulations standardized by Indonesian national standards; and 2) the community's response to the planning for the construction of a landfill is positive, considering that the community agrees with the review to avoid new problems.